Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Dubatolov, Vladimir V.; Kishida, Yasunori (Zootaxa, 2017)
The new genus Barsura Volynkin, Dubatolov & Kishida, gen. nov. is described for Barsine nubifascia Walker, 1864. Three new species, B. clandestina Volynkin, Dubatolov & Kishida, sp. nov., B. obscura Volynkin, Dubatolov & Kishida, sp. nov. and B. contrastata Volynkin, Dubatolov & Kishida, sp. nov. are described from China. B. simplicifascia (Elwes, 1890), stat. nov. is upgraded to the species level. Three species previously treated as Asura, B. lineata (Fang, 2000), comb. nov., B. melanoleuca (Hampson, 1894), comb. nov. and B. umbrifera (Hampson, 1900), comb. nov. are transferred to Barsura, and one species, Barsine umbrosa (Hampson, 1896) comb. nov. is transferred to Barsine. The name lineata Fang, 1993 is restored as valid. Adults, male and female genitalia of all Barsura species and representatives of the related genera Barsine and Asura are illustrated.